2016
DOI: 10.1142/s0218127416300263
|View full text |Cite
|
Sign up to set email alerts
|

Switching Dynamics Between Two Movement Patterns Varies According to Time Interval

Abstract: This study investigated the regularity that characterizes the behavior of dissipative dynamical systems excited by external temporal inputs for pointing movements. Right-handed healthy male participants were asked to continuously point their right index finger at two light-emitting diodes (LEDs) located in the oblique left and right directions in front of them. These movements were performed under two conditions: one in which the direction was repeated and one in which the directions were switched on a stochas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…this is considered an excited attractor. Recent studies based on this dynamical systems theory, for example not only the physical phenomenon [Arecchi et al, 1986;Constantin et al, 1991;Maas et al, 1997;Matias et al, 1997;Mestl et al, 1997;Schmiegel & Eckhardt, 1997;Tanii et al, 1999;Tanii et al, 1991] but also human movement [Hirakawa et al, 2016;Suzuki & Yamamoto, 2015;Yamamoto & Gohara, 2000], have revealed that the spatiotemporal structure in various natural phenomena is fractal-like and/or self-similar. These studies on human movement entailed tasks in which participants switched several different movement patterns continuously with the external inputs being abruptly switched.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…this is considered an excited attractor. Recent studies based on this dynamical systems theory, for example not only the physical phenomenon [Arecchi et al, 1986;Constantin et al, 1991;Maas et al, 1997;Matias et al, 1997;Mestl et al, 1997;Schmiegel & Eckhardt, 1997;Tanii et al, 1999;Tanii et al, 1991] but also human movement [Hirakawa et al, 2016;Suzuki & Yamamoto, 2015;Yamamoto & Gohara, 2000], have revealed that the spatiotemporal structure in various natural phenomena is fractal-like and/or self-similar. These studies on human movement entailed tasks in which participants switched several different movement patterns continuously with the external inputs being abruptly switched.…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical framework is detailed in the next section. Figure 1 shows schematics highlighting the difference between autonomous and nonautonomous systems [Hirakawa et al, 2016]. For instance, Figs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations